Dina sketi n. sp., a new erpobdellid leech (Hirudinida: Erpobdellidae) from Bosnia and Herzegovina - Grosser, Clemens; Pešić, Vladimir; Dmitrović, Dejan (Zootaxa, 2014)
The concept of the genera within the family Erpobdellidae seems to be extremely artificial. Recent phylogenetic studies (Trontelj & Sket 2000, Siddall 2002) based on morphology and DNA sequence data showed that a revision of the family was necessary because the morphological characters used to distinguish known erpobdellid genera are not informative. The pattern of annulations, traditionally used for distinguishing Dina Blanchard, 1892 and Trocheta Dutrochet, 1817 has been proven to be inappropriate for identification of some species (e.g. Dina krasensis (Sket, 1968) and D. pseudotrocheta Grosser & Eiseler, 2008; see Trontelj & Sket (2000) and Grosser et al. (2011b), respectively). Siddall (2002) synonymized all the erpobdellid genera with Erpobdella de Blainville in Lamarck, 1818. However we decided to retain the traditional generic subdivisions of Erpobdellidae in accordance with the reasons listed by Trontelj & Sket (2000), which were also followed by the recent taxonomic studies (e.g. Ben Ahmed et al. (2011). Further systematic studies should be conducted for revising classification of the erpobdellid genera.